(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This paper reports a theoretical review in which arts education is addressed as a device for strengthening knowledge, skills, competencies and basic skills in primary education so that students are formed in a comprehensive manner and with a thinking in which empathy and languages of peace are the protagonists for the construction of a supportive, inclusive and assertive world in the peaceful resolution of conflicts. In this regard, the authors addressed place art education as a motivating axis for the consolidation of actions that allow educators to integrate the knowledge established in the curricula, with sensory awareness and the acquisition of life skills, and in turn, they highlight primary basic education as the ideal time to motivate and contribute to the strengthening of these skills from environments of harmony, empathy and individual and collective maturity with a view to the construction and experience of peace scenarios. Thus, the invitation is generated so that from the schools of basic education the diverse artistic possibilities are adopted for the growth of the human being in all its dimensions, recognizing art as a scenario for peace and positive social transformation.